A review of Uganda’s Agricultural Policy and how it addresses AgriFose2030’s Target Groups - Mugagga, Frank; Kakooza, Lydia; Asiimwe, George (SLU Global, 2018)
This paper provides an overview of existing agricultural policies in Uganda and how they address the key AgriFose2030 target groups that include; smallholder farmers, women and youth. One of the main policies in Uganda’s agricultural sector is the National Agriculture Policy (NAP) which deals with commercialization of smallholder agriculture through accessibility of financial services such as, loans. However, NAP lacks a consistent and implementation framework thereby hindering proper transformation and increase of agricultural production in the sector. The Agriculture Sector Strategic Plan (ASSP) of 2015/16 to 2019/20 lays out the priorities and interventions that are crucial to transforming smallholder farmers into commercial farmers. The five year strategy focuses on improving the accessibility of critical farm inputs such as, fertilizers as wells value addition and markets for the agricultural produce. However, the strategy is constrained by unfavorable conditions for agricultural transformation such as, inadequate participation of women and youth and limited extension services. The National Agricultural Extension Policy (NAEP), 2016, was developed to provide long term strategic direction for agricultural extension services in Uganda. The agricultural extension services facilitate smallholder farmers to sustain agricultural production and shift from subsistence farming to market-oriented and commercial farming. However, there are some challenges faced by the implementation of the policy such as, reduced funding for agricultural extension service delivery in the national budget and insufficient human resource that is inadequate to implement the agricultural extension reforms. The National Agricultural Extension Strategy (NAES) 2016/17 to 2020/21 is expected to improve efficiency of agricultural production, competitiveness, and commercialization of smallholder farmers. The strategy empowers and allows participation of smallholder farmers, women, and youth so that they can benefit effectively from extension services and develop value chains that address their needs. In addition, NAES advocates for stronger linkages with research, educational and farmer institutions among smallholders to improve agricultural production. The National Fertilizer Policy of Uganda (2016) ensures availability of affordable, accessible, high quality, safe, profitable and sustainable fertilizer to smallholders to achieve sustainable production. The policy promotes awareness of fertilizers and encourages the participation of smallholders, women and youth in the marketing of fertilizers. However, smallholder farmers lack knowledge/information of how to improve soil fertility, their proper use, the high cost and poor supply in Uganda. Though not yet implemented, the Draft of National Seed Policy 2014 (NSP) ensures that smallholders have access to adequate, affordable, high quality and safe seed and planting material that is crucial for agricultural intensification. This policy focuses on increasing awareness, proper dissemination of seed related profitability information among smallholders to increase agricultural productivity. For example, the policy encourages smallholders, women and youth to conserve the best crop varieties with high food security value. The Draft Irrigation Policy and National Irrigation Master Plan for Uganda (2010-2035) has provision for smallholders that engage in subsistence farming and those who are shifting from subsistence farming to commercial farming to increase their agricultural production and productivity.
Keywords: Uganda; agricultural policy